CONDUCTING THE FIRST STAGE OF TRAINING WITH FOOTBALL PLAYERS THROUGH ACTION GAMES IN THE EDUCATIONAL AND LEARNING PROCESS - Mirzakarimova N. I. (Bright Mind Publishing, 2025)
This article considers the problems of monitoring and analyzing the physical activity of football players during the initial stages of physical training. The volume and intensity of football players' movements during the game are determined.
Keywords: Training football players for sports at the initial stage, means of developing the physical, technical and tactical training of key football players; specialized movement games and relay races in the process of training football players.